Implementation of narcotics rehabilitation policy in reducing addict addiction at the national narcotics agency of dki jakarta province - Emka Farah Mumtaz; Kusworo; Baharuddin Thaher; Tjahjo Suprajogo (Universitas Islam KH. Achmad Muzakki Syah Jember, 2026)
Narcotics abuse has emerged as a multidimensional governance challenge that requires a balanced approach between enforcement and rehabilitation, particularly in complex urban contexts. This study aims to analyze the implementation of narcotics rehabilitation policy at the National Narcotics Agency of DKI Jakarta Province, focusing on how policy is operationalized, the factors influencing its effectiveness, and its outcomes in reducing drug dependency. A qualitative case study approach was employed, utilizing in-depth interviews, observations, and document analysis to capture the interaction between institutional, structural, and socio-environmental dimensions. The findings reveal that although rehabilitation is formally prioritized within the policy framework, its implementation remains constrained by inconsistencies in operational interpretation, limited institutional resources, fragmented inter-agency coordination, and varying organizational commitment. In addition, socio-environmental factors, particularly stigma and uneven public awareness, significantly hinder access to rehabilitation services. The study further demonstrates that these dimensions operate in an interconnected and systemic manner, where weaknesses in one aspect reinforce challenges in others, ultimately shaping uneven policy outcomes. While the policy has contributed to increasing awareness and supporting recovery efforts, its long-term effectiveness remains dependent on the alignment of implementation factors. Theoretically, this study advances policy implementation literature by integrating regulatory, institutional, and socio-cultural dimensions into a comprehensive analytical framework. Practically, it offers strategic insights for improving rehabilitation policy through enhanced operational clarity, capacity strengthening, coordination mechanisms, and stigma reduction. Overall, this study provides a critical and contextually grounded understanding of how rehabilitation policies can be implemented more effectively to achieve sustainable and humane outcomes in narcotics governance.